VEGETABLE OIL BASED EPOXIDIZED OIL: A SUSTAINABLE APPROACH - Mahazmi Burhanuddin Mahadi; Mohd Jumain Jalil; Mariam A. Rahman; Ismail Md. Rasib; Intan Suhada Azmi (Journal of Islamic, Social, Economics and Development, 2022)
The fatty acid content in vegetable oil will undergo epoxidation reaction to produce epoxide. The epoxidation reaction was to modify the structure of carbon-carbon double bond by removing unsaturated content into oxirane oxygen ring by using the oxidizing agents, that improved the oxidative stability of epoxide. The study of a greener epoxidation by using vegetable oil to produce an eco-friendly epoxide was increasing every year. Epoxidation of oleic acid was carried out by in situ performic acid to produce epoxidized oil. Since epoxide ring is highly reactive, the degradation of the oxirane was examine using water. Then, kinetic study was carried by developed a single-phase kinetic model to determine the value of kinetic rate constant, k for every reaction via MATLAB simulation. From the results of simulation data, it was proved that, epoxidtion have different reaction rate for different catalyst applied in epoxidation process.